Poetic tendencies in contemporary Croatian playwriting - Ljubic´, Lucija (Amfiteater (Ljubljana), 2022)
The paper offers an overview of the most prominent poetic tendencies in contemporary Croatian playwriting after the year 2000. Focusing on several well-known Croatian playwrights (such as Mate Matišić, Davor Špišić, Ivan Vidić, Nina Mitrović, Elvis Bošnjak, Dubravko Mihanović, Tomislav Zajec, Ivana Sajko, Tena Štivičić, Ivor Martinić, Olja Lozica ...) whose plays have been staged, published, studied and/or rewarded over the past two decades in both Croatia and abroad, the paper looks into the features of the subject matter (local or global, public or intimate, popular or provocative concerns), the formal and generic qualities (dramatic structure, narration, poetisation, exploration of the limits of playwriting), the representation of cultural identities (personal and collective), the interest in mass and popular culture, the characteristics of dramatic discourse and language, the relation towards social engagement or criticism, and the effort to appeal to targeted social groups or types of audiences. The paper explores the differences and similarities between the playwriting of the 1990s and playwriting after 2000.
Keywords: contemporary Croatian playwriting; Croatian theatre repertoire; generacije hrvaških dramatikov in dramatičark; generations of Croatianplaywrights; gledališke revije; Marin Držić award; nagrada Marina Držića; postdramatic writing; postdramsko pisanje; promocija hrvaške dramatike; promotion of Croatina playwriting; repertoar hrvaškega gledališča; sodobna hrvaška dramatika; theatre journals